2016
DOI: 10.1021/acs.est.5b05583
|View full text |Cite
|
Sign up to set email alerts
|

Organic Contaminants in Chinese Sewage Sludge: A Meta-Analysis of the Literature of the Past 30 Years

Abstract: The production of sewage sludge is increasing in China but with unsafe disposal practices, causing potential risk to human health and the environment. Using literature from the past 30 years (N = 159), we conducted a meta-analysis of organic contaminants (OCs) in Chinese sludge. Most data were available from developed and populated regions, and no data were found for Tibet. Since 1987, 35 classes of chemicals consisting of 749 individual compounds and 1 mixture have been analyzed, in which antibiotics and poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(57 citation statements)
references
References 136 publications
(199 reference statements)
1
55
0
1
Order By: Relevance
“…Numerous studies have demonstrated that the discharge from WWTPs is one of the largest sources for new-emerging organic pollutants to natural environment [1] [3] [9] [10]. Many NEOPs are derived from the public's daily life, such as the highlighted PPCPs, then discharged and entered into the WWTPs directly [8].…”
Section: Possible Reasons For the Wide Occurrence Of Neopsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that the discharge from WWTPs is one of the largest sources for new-emerging organic pollutants to natural environment [1] [3] [9] [10]. Many NEOPs are derived from the public's daily life, such as the highlighted PPCPs, then discharged and entered into the WWTPs directly [8].…”
Section: Possible Reasons For the Wide Occurrence Of Neopsmentioning
confidence: 99%
“…As the social and industrial development, more and more new-emerging organic pollutants (NEOPs), such as the pharmaceuticals and personal care products (PPCPs), were detected in natural environments [1], and have been enormously documented to be devastating to ecological biodiversity and public health [2] [3] [4] [5]. But the intentions and measures taken to deal with the environmental health problem are weak.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] They are used as additives and antioxidants in plastics,a nd widely in surfactants, detergents, pesticides, and industrial environments. [4] They also occur as environmental residues,i ncluding in food [5] and food packaging materials, [6] water, [7][8][9] soil, and air. [10] Many studies have reported that long-term exposure to NPNs can affect the normal reproduction and development of organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The sludge contains not only harmful substances such as heavy metals, pathogenic microorganisms, refractory organic matter, but also a large number of organic matter that can be used. If it is used effectively, it will produce very considerable economic and social benefits [1][2]. At present, the main problems to be solved in sludge treatment are sludge reduction, stabilization, harmless and resource treatment, and pyrolysis is one of the effective ways to solve this problem.…”
Section: Introductionmentioning
confidence: 99%